Controlling polio outbreak due to imported wild poliovirus in Indonesia: A success story - Sumarmo Poorwo Soedarmo; Sidik Utoro (Paediatrica Indonesiana, 2009)
Background As a WHO member state, Indonesia is committed toGlobal Polio Eradication. The last indigenous polio case was found in 1995. However, we faced a big challenge with the occurrence of polio outbreak, beginning with a polio case caused by imported wild poliovirus (WPV) type 1 in Sukabumi in 2005. The virus was originated from Sudan and imported to Indonesia through Saudi Arabia. The outbreak ended with totally 305 cases throughout the country. The last one occurred on 20 February 2006 in Aceh Tenggara District, Nanggroe Aceh Darussalam Province. In addition and separated from the WPV type 1 outbreak, in August 2005, four Acute Flaccid Paralysis (AFP) cases with type 1 Vaccine Derived Poliovirus (VDPV) in stool samples were identified in Madura, East Java Province. The first case was on 9 June 2005 and ended with 45 cases in Madura and another case in Probolinggo District, East Jawa.Objective To report a success of controlling outbreak of importedWPV in Indonesia.Methods Outbreak Response Immunization (ORI) and mopup immunization were conducted immediately. To completelystop the transmission, three rounds of National ImmunizationDays (NIDs) were conducted in 2005 (August, September, andNovember). Some more Supplementary Immunization Activities(SIAs) were conducted in 2006 (mop up in January, NIDs inFebruary and early April, mop ups in June and August 2006).For the VDPV outbreak, ORI of 18,880 children in 83 villagestook place during the first week of August, beside three roundsofNIDs in 2005.Results All activities resulted in satisfactorily coverage, whereeach round always exceeded 95%.Conclusions Those activities were conducted successfully andproven to be effective to stop the outbreak. Then again, Indonesia can be a polio free country in the coming years.